2015
DOI: 10.5194/se-6-323-2015
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt, chromium and nickel contents in soils and plants from a serpentinite quarry

Abstract: Abstract. The former serpentinite quarry of Penas Albas (Moeche, Galicia, NW Spain) left behind a large amount of waste material scattered over the surrounding area, as well as tailing areas. In this area several soils were studied together with the vegetation growing spontaneously over them with the aim of identifying the bioavailability of heavy metals. The potential of spontaneous vegetation for phytoremediation and/or phytostabilization was evaluated. The pH of the soils ranges from neutral to basic, with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 51 publications
4
38
1
Order By: Relevance
“…All species, both in above-underground parts are characterized by the highest contents of Ni followed by Cr and Co. The same tendency was observed in other studies independently the climate conditions (Kataeva et al 2004;Reeves et al 2007a;Reeves et al 2007b;Lago-Vila et al 2015). For example, leaves of Bonamia mexicana from Santa Elena peninsula (Costa Rica) accumulated 12 mg kg −1 of Ni followed by 0.5 mg kg −1 of Cr and 0.1 mg kg −1 of Co.…”
Section: Accumulation Of Metals By Plantssupporting
confidence: 68%
See 2 more Smart Citations
“…All species, both in above-underground parts are characterized by the highest contents of Ni followed by Cr and Co. The same tendency was observed in other studies independently the climate conditions (Kataeva et al 2004;Reeves et al 2007a;Reeves et al 2007b;Lago-Vila et al 2015). For example, leaves of Bonamia mexicana from Santa Elena peninsula (Costa Rica) accumulated 12 mg kg −1 of Ni followed by 0.5 mg kg −1 of Cr and 0.1 mg kg −1 of Co.…”
Section: Accumulation Of Metals By Plantssupporting
confidence: 68%
“…The competition between Ca and metals was observed by other authors (Li et al 2009;Wang et al 2010;Yusuf et al 2011;Lago-Vila et al 2015;Aziz et al 2015). For example, Li et al (2009) andLago-Vila et al (2015) suggested that exchangeable Ca can decrease Ni and Co accumulation by plants because of competition for binding sites in root cells. Furthermore, Wang et al (2010) , Ni 2+ in Triticum aestivum and Pisum sativum.…”
Section: Accumulation Of Metals By Plantsmentioning
confidence: 62%
See 1 more Smart Citation
“…These are higher than the (11,50,100,150,250) mg/kg stipulated standards on agricultural soil by US EPA [40], EPAA [41], WHO [42], EU [43], and CME [44] respectively. Similarly, Lago-Vila et al [45] on analysis of quarry site soil stated a higher Cr level 1300 µg/g in a studied soil. Fosu-Mensah et al [46] on the contrary established a lower chromium level 56.0±1.15 µg/g in soils and vegetation of Korle lagoon.…”
Section: Statistical Data Analysismentioning
confidence: 63%
“…soil pH increased after calcium oxide, zeolite and manure were added to it. An increase in the soil pH promotes the immobilisation of cobalt in a soil solution, thereby reducing its toxicity to plants (Lago-Vila et al, 2015;Li et al, 2009;Wendling et al, 2009). A significant effect of pH and CaCO 3 on the content of cobalt in soil was suggested by Kabir et al (2014).…”
Section: Figmentioning
confidence: 97%